2019
DOI: 10.14267/veztud.2019.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Bank – FinTech együttműködés – avagy a megújulás kulcsa a pénzügyi szolgáltatások piacán?

Abstract: The rise of customer-oriented banking-electronic markets are paving the way for change in the financial industry. Electron Markets, 22, p. 203-215.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Many FinTech studies (Arha & Jufri, 2020;Jutla & Sundararajan, 2016;Lee & Shin, 2018;Varga, 2017) explored the FinTech value drivers, ecosystem, and its elements, while Csepy & Aranyossy (2019) were focusing on the customer value creation power in the financial services industry. Although Phat Pham et al (2021) categorized FinTech as "bank FinTech" (traditional financial institutions utilizing financial technologies) and as "Fin-Tech-outside" (non-financial institutes using technology to provide financial services) -which viewpoint and sector-specific analysis also assessed by other authors (Gyüre, 2020;Horváth, 2019Horváth, , 2020Kerényi & Molnár, 2017) -, it can be concluded that the definition of Fin-Tech is very versatile and can be approached from many sides. Another relevant angle is the importance of Fin-Tech solutions in the field of green finance (MNB, 2022;Horvath, 2022), which can contribute to the aim of green financing and broadly, to GreenTech solutions -supporting green objectives and investments.…”
Section: Figure 3 the Everythingtech Phenomenon In Various Industriesmentioning
confidence: 99%
“…Many FinTech studies (Arha & Jufri, 2020;Jutla & Sundararajan, 2016;Lee & Shin, 2018;Varga, 2017) explored the FinTech value drivers, ecosystem, and its elements, while Csepy & Aranyossy (2019) were focusing on the customer value creation power in the financial services industry. Although Phat Pham et al (2021) categorized FinTech as "bank FinTech" (traditional financial institutions utilizing financial technologies) and as "Fin-Tech-outside" (non-financial institutes using technology to provide financial services) -which viewpoint and sector-specific analysis also assessed by other authors (Gyüre, 2020;Horváth, 2019Horváth, , 2020Kerényi & Molnár, 2017) -, it can be concluded that the definition of Fin-Tech is very versatile and can be approached from many sides. Another relevant angle is the importance of Fin-Tech solutions in the field of green finance (MNB, 2022;Horvath, 2022), which can contribute to the aim of green financing and broadly, to GreenTech solutions -supporting green objectives and investments.…”
Section: Figure 3 the Everythingtech Phenomenon In Various Industriesmentioning
confidence: 99%
“…The continuous cuts in municipal budgets for public services before 2010 indeed worsened the quality of public services. However, empirical analyses show that the nationalisation of these functions has not contributed to improving quality (ÁROP 2012;KÖFOP 2017;Horváth 2014Horváth , 2015.…”
Section: Changes and Acceptance Of The Municipal Task Systemmentioning
confidence: 99%
“…Demeter, Losonci, Nagy és Horváth (2019) egy magyar multinacionális vállalat példáján keresztül mutatja be az Ipar 4.0 adaptálását, az ezzel kapcsolatos lehetőségeket, nehézségeket és tapasztalatokat. Horváth (2019) a hagyományos és digitális gazdaság együttműködését és lehetséges szinergiáit vázolja a bankok és a FinTech cégek vonatkozásában. Horváth és Szabó (2019) pedig az Ipar 4.0 bevezetésének hajtóerőit, és korlátait, valamint a különböző cégek (multinacionális vállalatok, illetve kis-és középvállalatok) eltérő és hasonló lehetőségeit mutatják be.…”
Section: Cikkek Tanulmányokunclassified